Analyzing of BI Rate, Exchange Rate, and Money Supply on Inflation: Evidence from Indonesia - Utma, Siti Syafaatul; Sari, Emilda (WELFARE Jurnal Ilmu Ekonomi, 2025)
Economic stability is a fundamental concern faced by every nation, with monetary policy serving as a primary tool to maintain such stability, particularly in controlling inflation. This study aims to examine the impact of the Bank Indonesia interest rate (BI Rate), currency exchange rate, and money supply on the inflation rate in Indonesia. A quantitative research method was used with secondary data obtained from official publications of Bank Indonesia and the Central Statistics Agency (Badan Pusat Statistik). The study utilizes monthly time-series data covering the period from January 2021 to December 2024. In this research, inflation serves as the dependent variable, while the BI Rate, currency exchange rate, and money supply act as independent variables. The empirical results show that the currency exchange rate and money supply have a significant influence on inflation, whereas the BI Rate does not. These findings indicate that managing the exchange rate and controlling money supply are effective measures to maintain price stability. Furthermore, Bank Indonesia adopts the Inflation Targeting Framework (ITF) supported by a floating exchange rate system and Open Market Operations (OMO) to ensure macroeconomic stability. Stabilitas ekonomi merupakan aspek krusial yang dihadapi oleh setiap negara, dengan kebijakan moneter sebagai instrumen utama dalam menjaga keseimbangan dan mengendalikan inflasi. Penelitian ini bertujuan untuk menganalisis pengaruh suku bunga Bank Indonesia (BI Rate), nilai tukar mata uang, dan jumlah uang beredar terhadap tingkat inflasi di Indonesia. Pendekatan penelitian yang digunakan bersifat kuantitatif dengan memanfaatkan data sekunder yang diperoleh dari publikasi resmi Bank Indonesia dan Badan Pusat Statistik (BPS). Data yang digunakan berupa data bulanan dari Januari 2021 hingga Desember 2024. Hasil penelitian menunjukkan bahwa nilai tukar mata uang dan jumlah uang beredar berpengaruh signifikan terhadap inflasi, sedangkan BI Rate tidak memiliki pengaruh yang signifikan. Temuan ini mengindikasikan bahwa pengelolaan nilai tukar dan pengendalian jumlah uang beredar merupakan kebijakan efektif untuk menjaga stabilitas harga. Bank Indonesia menerapkan Kerangka Target Inflasi (Inflation Targeting Framework) dan Operasi Pasar Terbuka sebagai instrumen utama dalam memperkuat stabilitas makroekonomi.